KOMUNIKASI POLITIK ANGGOTA DPRD KOTA PEKANBARU TERPILIH PARTAI NASIONAL DEMOKRAT (NASDEM) DAN PARTAI KEBANGKITAN BANGSA (PKB) PADA PEMILIHAN UMUM TAHUN 2024 - Nugraha, Muhammad Fathan; ,, Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
In the 2024 general election in Pekanbaru City, the National Democratic Party (Nasdem) and the National Awakening Party (PKB) gained an increase in the number of votes and seats in the Pekanbaru City DPRD, from these results of course there are efforts made by the elected DPRD members of the Nasdem Party and the National Awakening Party (PKB) of Pekanbaru City in the form of political communication where by carrying out political communication the DPRD members can be elected as people's representatives in parliament. This study shows the form of political communication carried out by the elected DPRD members of the National Democratic Party (Nasdem) and the National Awakening Party (PKB) in the 2024 general election in Pekanbaru City. This study uses Harold D. Lasswell's political communication theory which includes five components, namely Who, Say What, In Which Channel¸ To Whom, and What The Effect. This research uses a descriptive qualitative method with data collection techniques by interview and documentation with triangulation data analysis techniques where data acquisition comes from various sources of informants whose data are taken. The data obtained from the selected informants are elected DPRD members of the National Democratic Party (Nasdem) and the National Awakening Party (PKB) of Pekanbaru City. The results of this study show how the form of political communication of the elected DPRD Members of the National Democratic Party (Nasdem) and the National Awakening Party (PKB) in the 2024 general election in Pekanbaru City with 5 components of Harold D. Lasswell's Political Communication theory which shows the people who become communicators in campaigning, campaign messages, media used in campaigning, targets in campaigning and also the influence obtained from the community, namely providing support to the elected DPRD Members of Pekanbaru City and increasing the number of seats obtained by the National Democratic Party (Nasdem) and the National Awakening Party (PKB) in the 2024 general election in Pekanbaru City. Keyword: Political Communication, Partai Nasional Demokrat (Nasdem), Partai Kebangkitan Bangsa (PKB)